SARS-CoV-2 Interference of Influenza Virus Replication in Syrian Hamsters - Halfmann, Peter J; Nakajima, Noriko; Sato, Yuko; Takahashi, Kenta; Accola, Molly; Chiba, Shiho; Fan, Shufang; Neumann, Gabriele; Rehrauer, William; Suzuki, Tadaki; Kawaoka, Yoshihiro (The Journal of infectious diseases, 2022)
Abstract In hamsters, SARS-CoV-2 infection at the same time as or before H3N2 influenza virus infection resulted in significantly reduced influenza virus titers in the lungs and nasal turbinates. This interference may be correlated with SARS-CoV-2–induced expression of MX1. In hamsters, a previous infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) interferes with a sequential infection with influenza virus (H3N2 subtype). The induction of the interferon-stimulated gene MX1induced by SARS-CoV-2 infection may play a partial role in the interference with this influenza subtype.